Intervensi Psikologis Layanan Konseling Digital terhadap Kecemasan Politik Masyarakat Urban Indonesia di Era Post-truth - Diyanatil Azkiya; Imam Lukmanul Hakim; Afif Fadli (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
This study discusses the effectiveness of digital counseling services as a form of psychological intervention in reducing political anxiety among urban Indonesians in the post-truth era. This era is characterized by the massive spread of information that is often misleading and triggers public uncertainty and unrest, especially before and during political processes such as elections. Using a qualitative approach with case study methods and in-depth interviews, this study explores the experiences of urban individuals who participate in digital counseling services. The results show that digital counseling is able to provide a reflective and supportive space for individuals to understand and manage their emotions and political perceptions in a healthier way. This intervention has been shown to strengthen psychological resilience, reduce levels of political anxiety, and increase media literacy and critical awareness of urban communities towards national political dynamics. These findings recommend the integration of digital mental health services into psycho-political impact mitigation strategies in the digital era.